The role of network relationships in small wineries' internationalization: A case study from Marche, Italy. Issue 1 (13th March 2017) - Vissak, Tiia; Francioni, Barbara; Musso, Fabio
Abstract : Purpose: This paper aims to examine the role of tourist-generated and other network relationships in small Italian wineries' internationalization. Design/methodology/approach: It is based on 14 cases of which four are discussed in detail. All 14 cases are summarized in two tables and analyzed in the Discussion section. Findings: Most firms did not pre-plan their foreign activities. International wine tourism was a major source for creating the contacts necessary for their internationalization: they created relationships/networks in tourists' home markets and, as a result, expanded there either through selling directly to tourists or to the importers they recommended. In addition, they relied on contacts created at trade fairs or by friends/relatives. Some internationalization attempts failed, as the firms were passive and lacked long-term strategic plans. Thus, these producers have not fully realized the potential of wine tourists' contacts and other network relationships in their internationalization. Originality/value: It shows how wineries benefited from tourists' networks and other co-operative relationships and how, as a result, they started exporting, but also which problems they faced. These topics have not received considerable research attention yet.